Independent segregation of two antigenic specificities (VP3 and VP7) involved in neutralization of rotavirus infectivity. - Hoshino, Y (1985)
Antiserum prepared against the M37 strain of rotavirus, recovered from an asymptomatic newborn infant in Venezuela, neutralized two prototype human rotaviruses that define two separate serotypes: serotype 1 (Wa) and serotype 4 (ST3). Thus, the M37 strain is a naturally occurring intertypic rotavirus. Analysis of reassortant viruses produced during coinfection in vitro indicated that the observed dual serotype specificity of M37 resulted from sharing a related outer capsid protein, VP3, with the ST3 virus and another related outer capsid protein, VP7, with the Wa virus. Analysis of single (VP3)-gene-substitution reassortants indicated that VP3 was as potent an immunogen as VP7. In addition, direct evidence was obtained that the serotype specificity of neutralizing antibody elicited by VP3 can differ from the serotype specificity of neutralizing antibody elicited by VP7, indicating the need for a dual system of rotavirus classification in which the neutralization specificity of both VP3 and VP7 outer capsid proteins are identified.